2019
DOI: 10.1101/793794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SKIPHOS: non-kinase specific phosphorylation site prediction with random forests and amino acid skip-gram embeddings

Abstract: Phosphorylation, which is catalyzed by kinase proteins, is in the top two most common and widely studied types of known essential post-translation protein modification (PTM). Phosphorylation is known to regulate most cellular processes such as protein synthesis, cell division, signal transduction, cell growth, development and aging. Various phosphorylation site prediction models have been developed, which can be broadly categorized as being kinasespecific or non-kinase specific (general). Unlike the latter, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…We calculated the Sn, Sp, MCC, and AUC values to measure the model's performance. Many well-known prediction tools were compared, including GPS2.1 [31], NetPhos [32], PPRED [33], Musite [23], PhosphoSVM [21], SKIPHOS [34], and DeepPhos [27]. The results showed that our model outperformed all other models for the S and T sites.…”
Section: Comparison With Existing Phosphorylation Site Prediction Toolsmentioning
confidence: 95%
“…We calculated the Sn, Sp, MCC, and AUC values to measure the model's performance. Many well-known prediction tools were compared, including GPS2.1 [31], NetPhos [32], PPRED [33], Musite [23], PhosphoSVM [21], SKIPHOS [34], and DeepPhos [27]. The results showed that our model outperformed all other models for the S and T sites.…”
Section: Comparison With Existing Phosphorylation Site Prediction Toolsmentioning
confidence: 95%
“…In this section, we provide a discussion of the comparative performance of Attenphos for general phosphorylation site prediction using a balanced dataset from human protein phosphorylation. We compared Attenphos with several existing general phosphorylation site prediction tools, including GPS 2.1 [12], NetPhos 3.0 [13], PPRED [14], Musite [15], PhosphoSVM [16], SKIPHOS [17], Deepphos [11], and Transphos [18]. We performed 10-fold cross-validation to train the model using the training datasets of the S, T, and Y sites.…”
Section: Comparison Experiments On Balanced Datasetsmentioning
confidence: 99%
“…In addition, biological properties are also used for prediction, such as with the GPS [14] and iGPS [15]; GPS uses the motif length selection (MLS) method, and iGPS is based on GPS [16] and adds information such as protein interactions to predict phosphorylation sites. Other prediction tools are non-specific [17], such as NetPhos [18] and DISPHOS [19]. NetPhos uses neural networks to predict the phosphorylation sites, while DISPHOS uses the amino acid frequency and disorder information to identify phosphorylation sites.…”
Section: Introductionmentioning
confidence: 99%